Enhancing reading skills among pre-service primary school teachers in Kazakhstan - Lazzat Sapartayeva; Sharban Maigeldiyeva (Institute of Advanced Engineering and Science, 2026)
Educators rely heavily on reading proficiency, but the reading habits of prospective teachers and their preparedness in teaching methods are frequently disregarded. In Kazakhstan, the preparedness of pre-service teachers to promote reading is still not fully understood despite the current educational reforms. This study fills the gap by offering Kazakhstan-focused knowledge on pre-service teachers’ reading habits and structural obstacles via a thorough mixed-methods approach. An explanatory sequential design was utilized. Data from 205 female pre-service primary school teachers at four universities in regions including Pavlodar, Karaganda, Shymkent, and Almaty were analyzed with the aid of descriptive statistics and analysis of variance (ANOVA). Data from 27 semi-structured interviews were evaluated through thematic analysis. The quantitative data showed a mix of opinions about leisure reading (mean (M)=3.09, standard deviation (SD)=1.44) and inadequate university preparation for teaching reading (M=3.05, SD=1.37). Participants reported digital reading fatigue with an average score of 3.07 and SD of 1.38, despite having frequent access to digital text. The qualitative data showed that time constraints (68%), academic overload (52%), and limited inclusion of practical applications in coursework were the primary obstacles. For Kazakhstani universities to develop effective future literacy role models, they must shift from purely theoretical instruction. Updating curricula with contemporary, culturally relevant texts and incorporating hands-on, peer-facilitated reading exercises is strongly advised to foster teacher confidence in instructional methods.